Chronic suppurative joint effusion due to burkholderia pseudomallei: A case report - Madhavi Deshmukh; Shailendra Mundhada (Wolters Kluwer Medknow Publications, 2013)
Burkholderia pseudomallei, a Gram-negative bacillus is the causative agent of Melioidosis, a glanders-like disease, primarily a disease of animals. Melioidosis has been only a rare and sporadic disease in humans outside its endemic region. Currently, diagnosis of B. pseudomallei in the clinical laboratory is very difficult, owing to low awareness of physicians to the nonspecific clinical manifestations, lack of responsiveness among microbiologists outside endemic areas, identification systems in the average sentinel laboratory, and the biosafety conditions necessary to process these organisms. We report a case of chronic left hip joint effusion in a known case of diabetes mellitus. Gram stain of computed tomography (CT)-guided aspirate from the joint revealed Gram-negative bacilli along with pus cells. Culture was confirmed as Burkholderia pseudomallei on Vitek2C, which was sensitive to ceftazidime and trimethoprim/sulfmethoxazole. Unfortunately, patient could not be started on appropriate antibiotics due to delay in detection and patient succumbed to severe septicemia. This case is reported to highlight importance of automated identification and sensitivity especially in nonendemic areas and unusual antibiogram of this organism for which disc diffusion method is not standardized.